Factors influencing access to kidney transplantation: a research protocol of a qualitative study on stakeholders’ perspectives - Steef Redeker; Jan J V Busschbach; Sohal Ismail; Katja Kloss; Lothar van Hoogdalem; Annemarie Luchtenburg; Jacqueline van de Wetering (BMJ Open)
Introduction Unequal access to kidney transplantation is suggested, but no systematic inventory exists about factors influencing access to kidney transplantation. There is an absence of any research that has combined stakeholder perspectives along the complete trajectory of transplantation. The present qualitative study explores the contributing factors from the perspectives of multiple stakeholders in this trajectory, including patients, health professionals and health insurance and financial representatives in the Netherlands. Moreover, stakeholders will be invited to suggesting strategies and solutions for handling the facilitating and hindering factors found. By means of interaction, stakeholder groups will arrive at a consensus for new policymaking in the field of a Dutch transplantation care.Methods and analysis The different stakeholders’ perspectives and possible solutions will be explored by interviewing in three phases. In the first phase, stakeholders’ group perspectives will be explored with individual interviews and focus group interviews without confrontation of views from other perspectives. In the second phase of focus group interviewing, perspectives will be confronted with the other stakeholders’ perspectives assessed. Finally, in the third phase, stakeholders will be invited to focus group discussions for suggesting solutions to overcome barriers and promote facilitators for improving access to transplantation. Approximately, groups from six to twelve participants per focus group and four to maximal six focus groups will be held per stakeholder, depending on the level of saturation, as prescribed by grounded theory. The interviews will be audio-recorded and transcribed verbatim, and qualitative data will be analysed according to the principles of grounded theory supported by using NVivo software.Ethics and dissemination The Medical Ethical Committee of Erasmus MC, Rotterdam, The Netherlands, has approved this study. The results will be disseminated in peer-reviewed journals and major international conferences.